Агрессивность и ассертивность в межкультурной коммуника- ции: от чёрной к белой риторике - Барышников, Николай (Acta Polono-Ruthenica, 2021)
This article presents the author’s interpretation of a new approach to the study of cross-cultural communication problems based on similarities of different cultures, whose representatives are partners in cross-cultural dialogue. From a humanistic standpoint, it is argued that there is an urgent need to change the paradigm of professional crosscultural communication from black rhetoric to white cross-cultural dialogue – a transition which can be implemented especially through the assertive behavior of its participants as an alternative to aggressive behavior. The main reasons for the insufficient effectiveness of cross-cultural dialogue with representatives of Russian culture are analyzed, including the historically conditioned unfriendly attitude of the world community towards Russia and foreign participants’ militant ethnocentrism.